La Rioja y la política económica regional española - Climent López, Eugenio (Geographicalia, 2017)
This work synthetically describes the regional economic policy set about in Spain since the creation of the Development Plans. Afterwards the paper pays attention to the case of La Rioja, which was seat of a Development Area and was subsequently incorporated to a Gran Area de Expansión. The results of such measurements are evaluated concluding with a positivs critical appraisal mude by the author.